Astroblastome de l'Enfant à propos d’un cas - ERRAAD Ibtissam; EL HIMRI Sami; BENTALEB Daouad, (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
Introduction: Astroblastoma is a rare primitive glial tumor found in children and young adults, preferentially located supratentorially. The aim of this article is to highlight the radiological features of this rare tumor on CT and MRI and to emphasize the challenges encountered during diagnosis. Case Report : We present the case of a 13-year-old girl diagnosed with astroblastoma, which manifested as intracranial hypertension syndrome and visual disturbances, and was confirmed through histopathological and molecular studies. Discussion : Astroblastoma is a glial tumor that is rarely reported in the literature. Clinical and radiological signs are non-specific and may mimic other differential diagnoses. Treatment is based on surgery and adjuvant radiochemotherapy. Conclusion : Although it is rare, astroblastoma should be included in the differential diagnosis of supratentorial tumors in children and young adults.Given itssometimes aggressive nature,early management and a multidisciplinary approach are important.